A composite photo-Fenton catalyst and its preparation method and application
By preparing microspherical TiO2-x/C/FeMn-LDHS/g-C3N4 composite photofenton catalyst, the problem of insufficient catalytic performance and stability of existing photocatalysts is solved, and efficient electron transfer and catalytic activity is achieved, which significantly improves the The removal efficiency of ammonia nitrogen and antibiotics in water bodies.
Patent Information
- Application Number
- CN202410874550.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-07-02
AI Technical Summary
The existing photocatalysts have shortcomings in catalytic performance and stability, especially the large band gap width of TiO2 and the agglomeration problems caused by the powder form, which reduces its quantum utilization and efficiency, poor visible light absorption capacity of g-C3N4 and surface reaction position. The limited point leads to its low photocatalytic efficiency.
TiO2-x/C/FeMn-LDHS/g-C3N4 composite photofenton catalyst was prepared by in-situ chemical reduction method, and TiO2-x hollow microspheres were coated with sodium carboxymethylcellulose after activation treatment. The carbon layer was formed, and the FeMn-LDHS layer was prepared by co-precipitation method, and it was compounded with g-C3N4 by chemical bath deposition method to form a heterojunction structure to improve electron transfer efficiency.
It significantly improves the photo response, absorption range and specific surface area of the catalyst, enhances the separation ability of electron-hole pairs, improves catalytic activity and removal efficiency, and has an efficient removal effect on ammonia nitrogen and lipophilic antibiotics in water.
Smart Images

Figure CN118616083B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, in particular to a microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst and its preparation method and application. Background Art
[0002] With the rapid development of global agriculture and industrialization, the discharge of domestic sewage and industrial wastewater has increased, and the concentration of nitrogen-containing compounds in sewage and wastewater has continued to rise, especially the increase in ammonia nitrogen content, which has aggravated the eutrophication of water bodies and seriously damaged the water ecological environment. At present, the main methods of denitrification include physical stripping, physical adsorption, biodegradation, chemical precipitation, electrochemical oxidation, breakpoint chlorination, etc. These methods are either costly or inefficient. Breakpoint chlorination will also produce residual chlorine. Therefore, a new denitrification technology with high efficiency, low cost and no secondary pollution is urgently needed. Since ammonia nitrogen and organic pollutants often occur at the same time, their simultaneous removal has very important application value.
[0003] Advanced Oxidation Process (AOP) s ) is a new type of oxidation treatment technology that has attracted much attention. It mainly works through the strong oxidizing substances (•OH, •Cl, •SO4, etc.) produced by the reaction. As a type of advanced oxidation technology, photocatalytic oxidation is considered to be an ideal method for effectively removing difficult-to-degrade organic matter and ammonia nitrogen. Photocatalytic oxidation technology is to add semiconductor photocatalysts to the reaction solution to produce •OH with strong oxidizing ability under the condition of ultraviolet or visible light irradiation. •OH undergoes redox reaction with pollutants to generate inorganic small molecules such as CO2. The photocatalytic oxidation technology treatment process not only has the characteristics of a wide range of applications, good removal effect, and no secondary pollution, but also has a good removal effect on certain special substances such as cyanide and bacteria.
[0004] The core of photocatalytic oxidation technology is semiconductor catalyst. TiO2 is a common semiconductor photocatalyst. Under light irradiation, the electrons inside the TiO2 photocatalyst are activated to form electron-hole pairs, which can form •OH with OH-, H2O and dissolved oxygen in water. It has the advantages of high catalytic activity, good stability, thorough mineralization, no secondary pollution, low cost and non-toxicity, and has become a research hotspot for semiconductor photocatalysts. It has good application prospects in environmental governance. However, the band gap of TiO2 is large, and the generated photogenerated electron-hole pairs are extremely easy to recombine during the transfer process; in addition, powdered TiO2 photocatalysts are prone to agglomeration, which reduces the specific surface area and leads to low quantum utilization of TiO2.
[0005] In recent years, a large number of studies have shown that coupling semiconductor materials with different bandgap widths is one of the effective ways to achieve visible light response characteristics and enhance their catalytic performance. Graphene-like carbon nitride (g-C3N4) is considered to be one of the best photocatalysts due to its narrow bandgap width (~2.7 eV), unique semiconductor band structure, excellent stability and non-toxicity. Currently, g-C3N4 is used in various photocatalytic reactions, including pollutant degradation, CO2 reduction and water photolysis. However, due to its poor ability to absorb visible light, low efficiency of photoinduced charge separation and limited surface reaction sites, the photocatalytic efficiency of g-C3N4 itself is relatively low. Therefore, it is urgently needed to modify it to improve the activity and stability of the catalyst.
[0006] Chinese patent document CN 113828294 A discloses a method for preparing a nano TiO2 / g-C3N4 photocatalytic material, firstly dissolving tetrabutyl titanate and urea in anhydrous ethanol to obtain a tetrabutyl titanate solution and a urea solution, then dropping the urea solution into the tetrabutyl titanate solution to obtain a mixed solution, dropping a mixed solution of deionized water and acetic acid into the mixed solution until a sol is formed; then drying the sol after aging, placing the obtained solid powder in a muffle furnace, heating to 500-600°C, sintering with insulation, and finally cooling to room temperature with the furnace, grinding, and obtaining the obtained material. Although this method is simple to operate and TiO2 and g-C3N4 are evenly mixed, the obtained powder is prone to agglomeration. Summary of the invention
[0007] In view of the shortcomings of existing photocatalysts, the purpose of the present invention is to provide a composite photo-Fenton catalyst with high catalytic performance, stable structure and significantly improved electron transfer efficiency, as well as a preparation method and application thereof.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] The first aspect of the present invention provides a microspherical TiO 2-x / C / FeMn-LDH S The preparation method of / g-C3N4 composite photo-Fenton catalyst, the specific technical scheme is as follows:
[0010] A microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst comprises the following steps:
[0011] (1) Using TiO2 hollow microspheres as raw materials, TiO 2-x Hollow microspheres, where 0.1≤x≤2;
[0012] (2) TiO 2-xThe hollow microspheres were activated and sodium carboxymethyl cellulose was coated on the activated TiO 2-x The surface of hollow microspheres is pyrolyzed and carbonized to obtain microspherical TiO 2-x / C;
[0013] (3) Using co-precipitation method on TiO 2-x / C surface to prepare manganese iron layered double hydroxide to obtain microspherical TiO 2-x / C / FeMn-LDH S ;
[0014] (4) TiO 2-x / C / FeMn-LDH S Composited with g-C3N4 by chemical bath deposition method to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
[0015] The second aspect of the present invention provides microspherical TiO prepared by the above preparation method. 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
[0016] The third aspect of the present invention provides the microspherical TiO 2-x / C / FeMn-LDH S Application of / g-C3N4 composite photo-Fenton catalyst in catalytic degradation of ammonia nitrogen and lipophilic antibiotics in sewage or sludge tail water.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. Microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst, hollow TiO2 microspheres, have good permeability and light utilization rate; and the reduced TiO 2-x Microspheres make the composite material have a higher light response and light absorption range; TiO 2-x The carbon layer on the surface can protect the Ti 3+ / O VS It is not oxidized, achieving efficient transfer of photogenerated electrons, thereby improving its catalytic performance and efficiency.
[0019] 2. TiO 2-x The amorphous carbon formed by carbonization of sodium carboxymethyl cellulose coated on the surface of the hollow spheres has a higher specific surface area, high porosity and good electron transfer ability compared to other carbon sources, providing more active sites for catalysis.
[0020] 3. Microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst, g-C3N4 and TiO 2-x The heterojunction structure between them can effectively transfer electrons and enhance the separation ability of photogenerated electron-hole pairs.
[0021] 4. Microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst, FeMn-LDH S Coated with TiO 2-x / C surface, the spherical and layered composite materials formed are beneficial to the improvement of catalyst performance, significantly increasing the specific surface area of the catalyst and improving the catalytic activity. The interlayer anions of the metal hydroxide can adsorb orthophosphate PO4 3- Phosphorus in the form of NH4 + Adsorption, showing a synergistic adsorption effect of nitrogen and phosphorus with amorphous carbon.
[0022] 5. Microspherical TiO 2-x / C / FeMn-LDH S The composite photo-Fenton catalyst of g-C3N4 is composed of iron-manganese hydroxide, g-C3N4, amorphous carbon and other materials with strong absorption effect on sunlight and visible light, which further enhances the absorption of sunlight and visible light by the photocatalyst and improves the photocatalytic efficiency. It is used as a photo-Fenton catalyst and has good effect in the efficient removal of ammonia nitrogen and lipophilic antibiotics in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 For TiO in Example 1 2-x Scanning electron micrographs of hollow microspheres at different magnifications.
[0024] Figure 2 For different TiO 2-x The mass ratio of hollow microspheres and sodium carboxymethyl cellulose is the product of microspherical TiO 2-x SEM images of TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:2; (b) TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:3; (c) TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:4; (d) TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:5; (e) TiO 2-xThe mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:6.
[0025] Figure 3 For TiO in Example 2 2-x The product microspherical TiO when the mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:4 2-x / Enlarged scanning electron microscope image of the C surface.
[0026] Figure 4 The microspherical TiO 2-x / SEM image of C.
[0027] Figure 5 The microspherical TiO 2-x / C / FeMn-LDH S Scanning electron microscopy images at different magnifications.
[0028] Figure 6 The microspherical TiO 2-x / C / FeMn-LDH S Scanning electron microscope image of / g-C3N4 composite photo-Fenton catalyst.
[0029] Figure 7 The microspherical TiO 2-x / C / FeMn-LDH S Transmission electron microscopy image of / g-C3N4 composite photo-Fenton catalyst.
[0030] Figure 8 The microspherical TiO 2-x / C / FeMn-LDH S X-ray diffraction pattern of / g-C3N4 composite photo-Fenton catalyst.
[0031] Fig. 9 The microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst and microspherical TiO2 / C / FeMn-LDH S Tauc plot of / g-C3N4 composite photo-Fenton catalyst.
[0032] Fig.10 Different TiO 2-x The mass ratio of hollow microspheres and sodium carboxymethyl cellulose in the microspherical TiO 2-x / C / FeMn-LDH S PL spectrum of / g-C3N4 composite photo-Fenton catalyst. DETAILED DESCRIPTION
[0033] The present invention designs and synthesizes a microspherical TiO2 with simple and controllable preparation, magnetic recovery, high catalytic performance and stable structure. 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst, TiO2 hollow microspheres were first synthesized by hydrothermal method, and TiO 2-x Hollow microspheres are then activated with dilute acid solution to hydroxylate the surface of the hollow microspheres; TiO 2-x The activated hydroxyl groups on the surface of hollow microspheres and the hydroxyl groups on the surface of sodium carboxymethyl cellulose (CMC-Na) form hydrogen bonds, allowing CMC-Na to be adsorbed on TiO 2-x The surface of hollow microspheres, after pyrolysis carbonization, CMC-Na on TiO 2-x The surface of the hollow microspheres is carbonized to form an amorphous carbon layer of 5-10 nm, which can protect the Ti 3+ / O VS Without being oxidized, Fe / Mn salt was used as a precursor and co-precipitated on TiO 2-x FeMn-LDHs were generated on the surface of the / C microspheres, and finally g-C3N4 was coated on the TiO 2-x / C / FeMn-LDH S On the surface, a catalyst with high catalytic performance and stable structure is prepared, which combines the advantages of spherical structure and layered structure, heterojunction, carbon protection and stable oxygen vacancies, and can significantly improve the electron transfer efficiency.
[0034] The microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst and its preparation method and application.
[0035] The first aspect of the present invention provides microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst comprises the following steps:
[0036] (1) Using TiO2 hollow microspheres as raw materials, TiO 2-x Hollow microspheres, where 0.1≤x≤2;
[0037] (2) TiO 2-x The hollow microspheres were activated and sodium carboxymethyl cellulose was coated on the activated TiO 2-x The surface of hollow microspheres is pyrolyzed and carbonized to obtain microspherical TiO 2-x / C;
[0038] (3) Using co-precipitation method to prepare microspherical TiO2-x / C surface to prepare manganese iron layered double hydroxide to obtain microspherical TiO 2-x / C / FeMn-LDH S ;
[0039] (4) Microspherical TiO 2-x / C / FeMn-LDH S Composited with g-C3N4 by chemical bath deposition method to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
[0040] In some embodiments of the present invention, in step (1), the preparation method of the TiO2 hollow microspheres comprises: using Ti salt as a precursor, ethanol as a solvent, and urea as an organic additive, and performing a hydrothermal reaction to prepare TiO2 hollow microspheres. In some embodiments of the present invention, the Ti salt is selected from any one of Ti(SO4)2, TiCl4, and Ti(S2O7)2. In some embodiments of the present invention, the molar ratio of the Ti salt to urea is 1:1~2. In some embodiments of the present invention, the ratio of the mass of urea to the volume of ethanol in the urea ethanol solution formed by the urea and ethanol is 0.02-0.05 g / mL. Preferably, the concentration of the ethanol is 95wt%. In some embodiments of the present invention, the reaction temperature of the hydrothermal reaction is 120~140℃, and the reaction time is 12~14 h.
[0041] In some embodiments of the present invention, in step (1), the in-situ chemical reduction method comprises adding TiO2 hollow microspheres to a reducing agent solution, performing a reduction reaction at room temperature, washing and drying to obtain TiO 2-x Hollow microspheres. In some embodiments of the present invention, the reducing agent is selected from any one or more of NaBH4, KBH4, and H2C2O4. Preferably, the solvent of the reducing agent solution is water, and the concentration of the reducing agent in the reducing agent solution is 0.1~0.5 mol / L. In some embodiments of the present invention, magnetic stirring is performed during the reduction reaction. In some embodiments of the present invention, the washing medium is water. In some embodiments of the present invention, the drying temperature of the drying is 60~80 ℃, and the drying time is 12~24 h.
[0042] In some embodiments of the present invention, in step (2), the activation treatment comprises treating TiO 2-x The hollow microspheres are placed in a dilute acid solution for ultrasonic treatment. In some embodiments of the present invention, the dilute acid solution is selected from any one of dilute hydrochloric acid, dilute nitric acid, dilute sulfuric acid, hydrofluoric acid, etc. In some embodiments of the present invention, the concentration of the dilute acid solution is 0.0005-0.01 mol / L.
[0043] In some embodiments of the present invention, in step (2), the sodium carboxymethyl cellulose is coated on the activated TiO 2-x The surface of the hollow microspheres includes: activated TiO 2-x The hollow microspheres are dispersed in a sodium carboxymethyl cellulose solution, so that the sodium carboxymethyl cellulose is coated on the activated TiO 2-x In some embodiments of the present invention, the TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:3-5. 2-x When the mass ratio of hollow microspheres to sodium carboxymethyl cellulose increases from 1:2 to 1:5, the TiO 2-x The carbon layer coverage on the surface of hollow microspheres gradually increased, but when the concentration of sodium carboxymethyl cellulose was too high (TiO 2-x When the mass ratio of hollow microspheres to sodium carboxymethyl cellulose was 1:6, it was not good. It was speculated that the excessive concentration of sodium carboxymethyl cellulose would cause it to self-assemble into a micellar structure and form a colloidal suspension, which would affect its adhesion to TiO 2-x The hollow microspheres are adsorbed on the surface, thus affecting the coating of the surface carbon layer; Figure 2 In figure e, we can see that a large number of cluster structures appear around the microspheres, which also confirms this point.
[0044] In some embodiments of the present invention, in step (2), the pyrolysis temperature is 400-600 °C, and the pyrolysis time is 3-5 h. In some embodiments of the present invention, the pyrolysis is performed by programmed heating, and the heating rate is 5-10 °C / min.
[0045] In some embodiments of the present invention, in step (2), the pyrolysis carbonization product needs to be washed, centrifuged, and dried to obtain microspherical TiO 2-x / C. In some embodiments of the present invention, the washing is washing with deionized water and ethanol in sequence. In some embodiments of the present invention, the drying temperature is 80-90°C and the drying time is 10-12 h.
[0046] In some embodiments of the present invention, in step (3), the coprecipitation method comprises the following steps: ultrasonically treating a mixed salt solution of a trivalent iron salt and a divalent manganese salt, and dropping the solution into a mixed alkaline solution of NaOH and Na2CO3, maintaining the pH at 9.5-10.5; after the addition is complete, adding microspherical TiO 2-x / C, ultrasonic treatment, after the precipitation reaction is complete, microspherical TiO 2-x / C / FeMn-LDH SIn some embodiments of the present invention, the mixed salt solution contains Fe 3+ , Mn 2+ The molar ratio of the trivalent iron salt and the divalent manganese salt is 1-2:1-5; preferably, the Fe 3+ The concentration of Mn is 0.1~1.0 mol / L. 2+ The concentration of the mixed salt solution is 0.1-1.0 mol / L. In some embodiments of the present invention, the trivalent iron salt and the microspherical TiO 2-x / C is 1~2:1. In some embodiments of the present invention, the temperature of the precipitation reaction is 150~170 °C, and the reaction time is 3~5 h. In some embodiments of the present invention, the ultrasonic treatment time is 10~20 min. In some embodiments of the present invention, the washing is sequentially washed with deionized water and ethanol; in some embodiments of the present invention, the drying method is vacuum drying, the drying temperature is 50~70 °C, and the drying time is 2~4 h.
[0047] In some embodiments of the present invention, in step (4), the chemical bath deposition method comprises: 2-x / C / FeMn-LDH S The g-C3N4 was dissolved in deionized water, ultrasonically treated, stirred and reacted, and the reaction product was washed and aged overnight to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst. In some embodiments of the present invention, the TiO 2-x / C / FeMn-LDH S In some embodiments of the present invention, the ultrasonic treatment time is 10 to 30 min. In some embodiments of the present invention, the washing is sequentially washed with deionized water and ethanol. In some embodiments of the present invention, the aging temperature is 55 to 65 ° C, and the aging time is 12 to 24 h.
[0048] The second aspect of the present invention provides the microspherical TiO 2-x / C / FeMn-LDH S The composite photo-Fenton catalyst prepared by the method for preparing the composite photo-Fenton catalyst of g-C3N4. Figure 1~2 , Figures 5 to 8 It can be seen that the composite photo-Fenton catalyst of the present invention comprises a four-layer structure, which is TiO 2-xThe hollow microspheres include an inner core layer, an amorphous carbon layer covering the outer core layer, an iron-manganese double hydroxide layer deposited on the surface of the amorphous carbon layer, and a g-C3N4 layer assembled on the surface of the iron-manganese double hydroxide layer.
[0049] The third aspect of the present invention provides the use of a composite photo-Fenton catalyst in catalytic degradation of ammonia nitrogen and lipophilic antibiotics in sewage or sludge tail water.
[0050] In some embodiments of the present invention, the composite photo-Fenton catalyst is used to catalyze the degradation of ammonia nitrogen and lipophilic antibiotics in sewage or sludge tail water, comprising the following steps: preparing microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst is added to water containing ammonia nitrogen and lipophilic antibiotics, H2O2 solution is added, and the mixture is placed under visible light for photocatalytic degradation. Preferably, the ammonia nitrogen concentration in the water is 10-50 mg / L, the lipophilic antibiotic concentration is 10-100 mg / L, the H2O2 solution dosage is 1.5-5.0 mL / L, the catalyst dosage is 10-50 mg / L, and the degradation time is 30-120 min.
[0051] In some embodiments of the present invention, the antibiotics include quinolone antibiotics, macrolide antibiotics, tetracycline antibiotics, sulfonamide antibiotics, etc. The quinolone antibiotics include norfloxacin, ciprofloxacin, enrofloxacin, ofloxacin, etc.; the macrolide antibiotics include azithromycin, erythromycin, etc.; the tetracycline antibiotics include tetracycline, chlortetracycline, oxytetracycline, etc.; the sulfonamide antibiotics include sulfamethazine, sulfamethoxazole, etc.
[0052] The specific embodiments of the present invention are further described in detail below in conjunction with preferred embodiments. When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, as those skilled in the art grasp the prior art and record the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0053] Example 1
[0054] A microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst comprises the following steps:
[0055] (1) Weigh 10 g Ti(SO4)2 and add it to a mixed solution of 2.5 g urea and 50 mL 95 wt% ethanol. Mix well. Then transfer the solution to a 150 mL polytetrafluoroethylene-lined reactor and react at 140 °C for 12 h. Cool naturally to room temperature and centrifuge. Wash the product with deionized water and ethanol several times, and dry it at 80 °C in vacuum for 12 h to obtain the product TiO2 hollow microspheres. Add the prepared hollow microspheres to 0.1 mol / L NaBH4 solution, stir magnetically at room temperature for 60 min, and finally wash with deionized water several times and dry at room temperature to obtain TiO 2-x Hollow microspheres; SEM characterization results of the product are as follows Figure 1 shown.
[0056] (2) Weigh 5 g TiO 2-x The hollow microspheres were placed in 20 mL of 0.0015 mol / L dilute nitric acid solution, ultrasonicated for 10 min, and dispersed in 70 mL of 0.82 mol / L sodium carboxymethyl cellulose solution (TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose was 1:3), ultrasonic treatment was performed for 20 min, and vacuum filtration was performed to separate the TiO 2-x The hollow microspheres were transferred to a muffle furnace, heated to 500 °C at a heating rate of 5 °C / min and kept warm for 5 h, and naturally cooled to room temperature. The product was washed several times with deionized water and ethanol, centrifuged, and vacuum dried at 85 °C for 10 h to obtain the product microspherical TiO 2-x / C, the SEM characterization results of the product are as follows Figure 2 As shown in b.
[0057] (3) A mixed salt solution of 25 mL, 1.0 mol / L Fe(NO3)3·9H2O and 25 mL, 1.0 mol / L Mn(NO3)2·4H2O was ultrasonicated for 20 min, and 7 g of microspherical TiO 2-x / C, stir evenly; dissolve 0.03 mol NaOH and 0.015 mol Na2CO3 in 100 mL water, stir for 30 min to form a mixed alkali solution; add the mixed alkali solution drop by drop into the mixed salt solution, keep the pH stable at 10, ultrasonicate for 30 min after the addition is completed, react at 150 ℃ for 3 h under oil bath conditions, cool naturally to room temperature, centrifuge, wash the product with deionized water and ethanol for several times, and vacuum dry at 70 ℃ for 3 h to obtain the product microspherical TiO 2-x / C / FeMn-LDH S The SEM characterization results of the products are as follows Figure 5shown.
[0058] (4) 3 g of microspherical TiO 2-x / C / FeMn-LHD S , 3 g g-C3N4 nanosheets were dissolved in 50 mL deionized water, ultrasonicated for 2 min, stirred at 35 °C for 3 h, and the product was washed with water and ethanol several times, respectively, and aged in an oven at 60 °C for 12 h to obtain microspherical TiO 2-x / C / FeMn-LHD S / g-C3N4 composite photo-Fenton catalyst, the SEM, TEM, and XRD characterization results of the product are shown in Figures 6-8 shown.
[0059] Figure 1 , Figure 2 Middle b, Figures 5 and 6 The following are scanning electron microscope images of the products obtained in each step of Example 1. Figure 1 It can be seen that the TiO prepared in step (1) of Example 1 2-x The hollow microsphere samples are microsphere-shaped; Figure 2 Middle b, Figures 5 and 6 Compared to Figure 1 It can be seen that the surface of the microspheres coated with the carbon layer becomes rougher than that of the TiO2 microspheres, and the surface of the microspheres further coated with bimetallic oxides and g-C3N4 becomes even rougher. The intuitive morphology and structure preliminarily indicate that the material composite is successful.
[0060] Figure 7 The microspherical TiO 2-x / C / FeMn-LDH S Transmission electron microscopy image of the / g-C3N4 composite photo-Fenton catalyst. Figure 7 It can be seen that the sample presents an obvious core-shell structure.
[0061] Figure 8 The microspherical TiO prepared in Example 1 2-x / C / FeMn-LDH SX-ray diffraction pattern of / g-C3N4 composite photo-Fenton catalyst. The material shows characteristic diffraction peaks of anatase TiO2 at 25.3°, 37.8°, 48.0°, 55.1° and 68.8° at 2θ, corresponding to (101), (004), (200), (211), and (116) crystal planes, respectively. It can be seen that TiO2 still retains its original characteristic diffraction peaks after being reduced, indicating that the structural characteristics of TiO2 are not affected by the reducing agent; the broad and weak diffraction peak at 21.5° is the diffraction peak of carbon, corresponding to the (002) crystal plane, and the decrease in the intensity of the characteristic diffraction peak may be attributed to the decrease in the intensity of the carbon diffraction peak. Due to the surface coating of LDH and g-C3N4, characteristic diffraction peaks of FeMn-LDO are shown at 24.2°, 31.4°, 37.5° and 41.4° at 2θ, corresponding to the (012), (104), (110) and (113) crystal planes, respectively, and two diffraction peaks at 12.9° and 27.7°, corresponding to the (100) and (002) crystal planes, respectively, which belong to the in-plane structural stacking and inter-plane stacking reflection of g-C3N4 corresponding to the conjugated aromatic system, further indicating that the material is successfully composited.
[0062] Example 2
[0063] A microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst comprises the following steps:
[0064] (1) Weigh 10 g Ti(SO4)2 and add it to a mixed solution of 2.5 g urea and 50 mL 95 wt% ethanol. Mix well. Then transfer the solution to a 150 mL polytetrafluoroethylene-lined reactor and react at 140 °C for 12 h. Then cool naturally to room temperature and centrifuge. The product is washed several times with deionized water and ethanol respectively and dried in vacuum at 80 °C for 12 h to obtain the product TiO 2-x The prepared hollow microspheres were added into 0.1 mol / L NaBH4 solution, stirred magnetically for 60 min at room temperature, and finally washed with deionized water and dried to obtain TiO 2-x Hollow microspheres.
[0065] (2) Weigh 5 g TiO 2-x The hollow microspheres were placed in 20 mL of 0.0015 mol / L dilute nitric acid solution, ultrasonicated for 10 min, and dispersed in 70 mL of 1.09 mol / L sodium carboxymethyl cellulose solution (TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose was 1:4), ultrasonic treatment was performed for 20 min, and vacuum filtration was performed to separate the TiO 2-xThe hollow microspheres were transferred to a muffle furnace, heated to 600 °C at a heating rate of 5 °C / min and kept warm for 5 h, and naturally cooled to room temperature. The product was washed several times with deionized water and ethanol, centrifuged, and vacuum dried at 85 °C for 10 h to obtain the product microspherical TiO 2-x / C, the SEM characterization results of the product are as follows Figure 2 Medium c and Figure 3 shown.
[0066] (3) A mixed salt solution of 25 mL, 1.0 mol / L Fe(NO3)3·9H2O and 25 mL, 1.0 mol / L Mn(NO3)2·4H2O was ultrasonicated for 20 min, and 7 g of microspherical TiO 2-x / C, stir evenly; dissolve 0.03 mol NaOH and 0.015 mol Na2CO3 in 100 mL water, stir for 30 min to form a mixed alkali solution; add the mixed alkali solution drop by drop into the mixed salt solution, keep the pH stable at 9.5, ultrasonicate for 30 min after the addition is completed, react at 150 ℃ for 5 h under oil bath conditions, cool naturally to room temperature, centrifuge, wash the product with deionized water and ethanol for several times, and vacuum dry at 70 ℃ for 3 h to obtain the product microspherical TiO 2-x / C / FeMn-LDH S .
[0067] (4) 3 g of microspherical TiO 2-x / C / FeMn-LHD S , 3 g g-C3N4 nanosheets were dissolved in 50 mL deionized water, ultrasonicated for 2 min, stirred at 35 °C for 3 h, and the product was washed with water and ethanol several times, respectively, and aged in an oven at 60 °C for 12 h to obtain microspherical TiO 2-x / C / FeMn-LHDS / g-C3N4 composite photo-Fenton catalyst.
[0068] Example 3
[0069] A microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst comprises the following steps:
[0070] (1) Weigh 10 g Ti(SO4)2 and add it to a mixed solution of 2.5 g urea and 50 mL 95 wt% ethanol. Mix well. Then transfer the solution to a 150 mL polytetrafluoroethylene-lined reactor and react at 130 °C for 12 h. Cool naturally to room temperature and centrifuge. Wash the product with deionized water and ethanol several times, and dry it at 80 °C in vacuum for 12 h to obtain the product TiO2 hollow microspheres. Add the prepared hollow microspheres to 0.1 mol / L NaBH4 solution, stir magnetically at room temperature for 60 min, and finally wash with deionized water and dry to obtain TiO 2-x Hollow microspheres.
[0071] (2) Weigh 5 g TiO 2-x The hollow microspheres were placed in 20 mL of 0.0015 mol / L dilute nitric acid solution, ultrasonicated for 10 min, and dispersed in 80 mL of 1.19 mol / L sodium carboxymethyl cellulose solution (TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose was 1:5), ultrasonic treatment was performed for 20 min, and vacuum filtration was performed to separate the TiO 2-x The hollow microspheres were transferred to a muffle furnace, heated to 500 °C at a heating rate of 5 °C / min and kept warm for 5 h, and then naturally cooled to room temperature. The product was washed several times with deionized water and ethanol, centrifuged, and vacuum dried at 85 °C for 10 h to obtain the product TiO 2-x / C hollow microspheres, the SEM characterization results of the products are shown in Figure 2 As shown in middle d.
[0072] (3) A mixed salt solution of 25 mL, 1.0 mol / L Fe(NO3)3·9H2O and 50 mL, 2.0 mol / L Mn(NO3)2·4H2O was ultrasonicated for 20 min, and 7 g of microspherical TiO 2-x / C, stir evenly; dissolve 0.03 mol NaOH and 0.015 mol Na2CO3 in 100 mL water, stir for 30 min to form a mixed alkali solution; add the mixed alkali solution drop by drop into the mixed salt solution, keep the pH stable at 10, ultrasonicate for 20 min after the addition is completed, react at 150 ℃ for 3 h under oil bath conditions, cool naturally to room temperature, centrifuge, wash the product with deionized water and ethanol for several times, and vacuum dry at 70 ℃ for 3 h to obtain the product microspherical TiO 2-x / C / FeMn-LDH S .
[0073] (4) 3 g of microspherical TiO 2-x / C / FeMn-LDHS , 4 g g-C3N4 nanosheets were dissolved in 50 mL deionized water, ultrasonicated for 2 min, stirred at 35 °C for 3 h, and the product was washed with deionized water and ethanol several times, respectively, and aged in an oven at 70 °C overnight to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
[0074] Comparative Example 1
[0075] Except for step (2), the carbon source is glucose, TiO 2-x The mass ratio of hollow microspheres to glucose is 1:3, in which TiO 2-x The hollow microspheres were 5 g, the volume of the glucose aqueous solution was 40 mL, the concentration was 2.08 mol / L, the pyrolysis carbonization temperature was 150°C, the time was 5 h, and the rest was the same as in Example 1. The SEM characterization results of the product are shown in Figure 4 shown.
[0076] Comparative Example 2
[0077] Except for step (2), TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:2, wherein the volume of sodium carboxymethyl cellulose solution is 70 mL, the concentration is 0.54 mol / L, and the rest is the same as in Example 1. The SEM characterization results of the product are shown in Figure 2 As shown in a.
[0078] Comparative Example 3
[0079] Except for step (2), TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:6, wherein the volume of sodium carboxymethyl cellulose solution is 70 mL, and the concentration is 1.63 mol / L. The rest is the same as in Example 1. The SEM characterization results of the product are shown in Figure 2 As shown in figure e.
[0080] Comparative Example 4
[0081] Except for step (1), TiO2 hollow microspheres are directly used instead of TiO 2-x Hollow microspheres are subjected to the same operation as in Example 1 except that steps (2) to (4) are performed to obtain a product in the form of microspherical TiO2 / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
[0082] Fig. 9 The microspherical TiO prepared in Example 1 and Comparative Example 4 2-x / C / FeMn-LDH S / g-C3N4 and microspherical TiO2 / C / FeMn-LDH S Tauc plot of / g-C3N4 composite photo-Fenton catalyst. Fig. 9 It can be seen that the microspherical TiO 2-x / C / FeMn-LDH S The absorption edge of / g-C3N4 red-shifted, and the optical band gap was 2.82 eV, which was lower than 2.7 eV of g-C3N4 and 3.2 eV of TiO2, indicating that the modified composite material has a wider light absorption range than single g-C3N4 and TiO2; at the same time, compared with the unreduced catalyst, the optical band gap is still dominant, indicating that the reduced TiO 2-x Microspheres can make the composite material have higher light response and light absorption range. The reduction of the band gap is related to the reduced Ti, which leads to the increase of the electronic state vacancy band, and the increase of the light absorption range may be due to the introduction of defects by Ti to improve the absorption of photon energy.
[0083] Fig.10 Different TiO 2-x The mass ratio of hollow microspheres and sodium carboxymethyl cellulose in the microspherical TiO 2-x / C / FeMn-LDH S PL spectrum of / g-C3N4 composite photo-Fenton catalyst. Fig.10 It can be seen that within a certain range, as the concentration of sodium carboxymethyl cellulose increases, the PL intensity gradually decreases, indicating that the carbon layer can inhibit the recombination of photogenerated electron-hole pairs during the transfer process and achieve efficient transfer of photogenerated electrons, thereby improving its catalytic performance and efficiency.
[0084] The microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 photo-Fenton catalyst and the products prepared in Comparative Examples 1 to 4 are used to remove ammonia nitrogen and antibiotics in water. The specific operation is as follows: weigh the microspherical TiO prepared in Examples 1 to 3 respectively. 2-x / C / FeMn-LDH S / g-C3N4 material, microspherical TiO prepared in step (3) of Example 1 2-x / C / FeMn-LDHs, microspherical TiO prepared in step (2) of Example 1 2-x / C, TiO prepared in step (1) of Example 1 2-x Hollow microspheres, microspherical TiO prepared in Comparative Examples 1 to 3 2-x / C / FeMn-LDH S / g-C3N4, microspherical TiO prepared in Comparative Examples 1 to 3 2-x / C and microspherical TiO2 / C / FeMn-LDH prepared in comparative example 4 S / g-C3N4, 30 mg each, the above materials were placed in 13 groups of 50 mL of solution containing 50 mg / L ammonia nitrogen and 50 mg / L tetracycline, numbered 1 to 13, and stirred in the dark for 30 min under the condition of shielding to achieve adsorption and desorption equilibrium; after the dark stirring, 1.5 mL of H2O2 solution was added, and the solution was placed under light for catalytic degradation, and the reaction time was 30 min. The results are shown in Table 1:
[0085] Table 1 Degradation rates of ammonia nitrogen and antibiotics in water by the catalysts prepared in the examples and comparative examples
[0086]
[0087] From the results in Table 1, it can be seen that the microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 photo-Fenton catalyst, with TiO 2-x Compared with the catalyst, it can greatly improve the removal efficiency of ammonia nitrogen and lipophilic antibiotics in water. 2-x / C through TiO 2-x The hollow microspheres are coated with an amorphous carbon layer to improve the catalytic performance. 2-x / C / FeMn-LDH S Further FeMn-LDH S Coated with TiO 2-x The spherical and layered composite materials formed on the surface of the carbon layer of / C significantly increase the specific surface area of the catalyst, improve the catalytic activity, and can also synergistically adsorb pollutants with the carbon layer. Therefore, the removal efficiency of ammonia nitrogen and lipophilic antibiotics is greatly improved; microspherical TiO 2-x / C / FeMn-LDH S Then it is compounded with g-C3N4 to obtain microspherical TiO with high catalytic performance and stable structure. 2-x / C / FeMn-LDH S / g-C3N4 photo-Fenton catalyst has the advantages of combining spherical structure with layered structure, heterojunction, carbon protection and stable oxygen vacancies, which significantly improves the electron transfer efficiency of the catalyst.
[0088] Comparative Example 1 uses glucose with the same mass ratio as in Example 1 as the carbon source, and the obtained TiO 2-x / C and TiO 2-x / C / FeMn-LDH SThe removal efficiency of ammonia nitrogen and lipophilic antibiotics in water by g-C3N4 is not as good as that of TiO in Example 1. 2-x / C and TiO 2-x / C / FeMn-LDH S / g-C3N4, indicating that the choice of carbon source has an important influence on the photocatalytic performance of the material. 2-x / C material scanning electron microscope image ( Figure 4 ) and the TiO obtained in Example 1 2-x / C material scanning electron microscope image ( Figure 2 (b) Microspherical TiO 2-x The surface morphology of the TiO / C materials is compared and it can be seen that the TiO 2-x The thinner carbon layer on the surface of the / C material may be attributed to the fact that glucose, as a monosaccharide, has a lower carbon content than sodium carboxymethyl cellulose. The concentration of sodium carboxymethyl cellulose solution in Comparative Example 2 is lower, resulting in the thinner surface of TiO 2-x The surface of the hollow microspheres is not completely covered with sodium carboxymethyl cellulose, and the obtained microspherical TiO 2-x / C The carbon layer on the surface of the material is unevenly distributed ( Figure 2 As shown in a), the photocatalytic performance is not as good as that of Examples 1 to 3. The concentration of sodium carboxymethyl cellulose solution in Comparative Example 3 is relatively high, resulting in the TiO 2-x Sodium carboxymethyl cellulose accumulates on the surface of hollow microspheres, and forms more cluster structures after carbonization ( Figure 2 e), and hindered the subsequent bimetallic deposition and the composite of the material and g-C3N4, resulting in the photocatalytic efficiency of the material being lower than that of Examples 1 to 3. The unreduced TiO2 composite catalyst obtained in Comparative Example 4 had relatively weak light response and light absorption range, resulting in the photocatalytic efficiency of the material being lower than that of Examples 1 to 3.
[0089] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A microspherical TiO 2-x / C / FeMn-LDH S A method for preparing a / g-C3N4 composite photo-Fenton catalyst, characterized in that: The following steps are involved: (1) TiO2 hollow microspheres were used as raw materials and TiO 2-x Hollow microspheres, where 0.1≤x≤2; (2) TiO 2-x The hollow microspheres were activated and sodium carboxymethyl cellulose was coated on the activated TiO 2-x The surface of hollow microspheres is pyrolyzed and carbonized to obtain microspherical TiO 2-x / C; the activation treatment comprises TiO 2-x The hollow microspheres were placed in a dilute acid solution for ultrasonic treatment; (3) Using co-precipitation method to prepare microspherical TiO 2-x / C surface to prepare manganese iron layered double hydroxide to obtain microspherical TiO 2-x / C / FeMn-LDH S ; (4) Microspherical TiO 2-x / C / FeMn-LDH S Composited with g-C3N4 by chemical bath deposition method to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst; the chemical bath deposition method comprises: 2-x / C / FeMn-LDH S The g-C3N4 was dissolved in deionized water, ultrasonically treated, stirred and reacted, and the reaction product was washed and aged overnight to obtain microspherical TiO 2-x / C / FeMn-LDH S / g-C3N4 composite photo-Fenton catalyst.
2. The preparation method according to claim 1, characterized in that In step (1), one or more of the following features are included: (1a) The method for preparing the TiO2 hollow microspheres comprises: using Ti salt as a precursor, ethanol as a solvent, and urea as an organic additive to perform a hydrothermal reaction to prepare the TiO2 hollow microspheres; (1b) The in-situ chemical reduction method comprises: adding TiO2 hollow microspheres to a reducing agent solution, performing a reduction reaction at room temperature, washing and drying to obtain TiO 2-x Hollow microspheres.
3. The preparation method according to claim 2, characterized in that: In step (1), one or more of the following features are included: (1a1) the Ti salt is selected from any one of Ti(SO4)2, TiCl4, and Ti(S2O7)2; (1a2) The molar ratio of the Ti salt to urea is 1:1-2; (1a3) in a urea-ethanol solution formed by urea and ethanol, the ratio of the mass of urea to the volume of ethanol is 0.02-0.05 g / mL; (1a4) the concentration of ethanol is 95wt%; (1a5) The reaction temperature of the hydrothermal reaction is 120 to 140° C., and the reaction time is 12 to 14 hours; (1b1) The reducing agent is selected from any one or more of NaBH4, KBH4, and H2C2O4; (1b2) the concentration of the reducing agent in the reducing agent solution is 0.1 to 0.5 mol / L; (1b3) performing magnetic stirring during the reduction reaction; (1b4) the washing medium is deionized water; (1b5) The drying temperature of the drying is 60 to 80° C., and the drying time is 12 to 24 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), one or more of the following features are included: (2b) The sodium carboxymethyl cellulose is coated on the activated TiO 2-x The surface of the hollow microspheres includes: activated TiO 2-x The hollow microspheres are dispersed in a sodium carboxymethyl cellulose solution, so that the sodium carboxymethyl cellulose is coated on the activated TiO 2-x Hollow microsphere surface; (2c) The pyrolysis temperature is 400-600° C. and the pyrolysis time is 3-5 h; (2d) The product after pyrolysis and carbonization needs to be washed, centrifuged, and dried to obtain microspherical TiO 2-x / C.
5. The preparation method according to claim 4, characterized in that: In step (2), one or more of the following features are included: (2a1) the dilute acid solution is selected from any one of dilute hydrochloric acid, dilute nitric acid, dilute sulfuric acid, and hydrofluoric acid; (2a2) The concentration of the dilute acid solution is 0.0005 to 0.01 mol / L; (2b1) TiO 2-x The mass ratio of hollow microspheres to sodium carboxymethyl cellulose is 1:3-5; (2c1) The pyrolysis is performed by programmed heating at a rate of 5 to 10°C / min; (2d1) The washing is performed by sequentially washing with deionized water and ethanol; (2d2) The drying temperature is 80-90°C and the drying time is 10-12 hours.
6. The preparation method according to claim 1, characterized in that: In step (3), the coprecipitation method comprises the following steps: ultrasonically treating a mixed salt solution of trivalent iron salt and divalent manganese salt, and dropping it into a mixed alkaline solution of NaOH and Na2CO3, maintaining the pH at 9.5 to 10.5; after the dropping is completed, adding microspherical TiO 2-x / C, ultrasonic treatment, after the precipitation reaction is complete, microspherical TiO 2-x / C / FeMn-LDH S .
7. The preparation method according to claim 6, characterized in that: Includes one or more of the following characteristics: (3a1) In step (3), the mixed salt solution contains Fe 3+ , Mn 2+ The molar ratio is 1-2:1-5; (3a2) In step (3), the trivalent iron salt and the microspherical TiO 2-x The mass ratio of / C is 1 to 2:1; (3a3) In step (3), the precipitation reaction temperature is 150-170° C., and the reaction time is 3-5 h; (3a4) In step (3), the ultrasonic treatment time is 10 to 20 minutes; (3a5) In step (3), the washing is performed by sequentially washing with deionized water and ethanol; (3a6) In step (3), the drying method is vacuum drying, the drying temperature is 50 to 70° C., and the drying time is 2 to 4 hours; (4a1) In step (4), the TiO 2-x / C / FeMn-LDH S , the mass ratio of g-C3N4 is 1:1~3; (4a2) In step (4), the ultrasonic treatment time is 10 to 30 minutes; (4a3) In step (4), the washing is performed by sequentially washing with deionized water and ethanol; (4a4) In step (4), the aging temperature is 55 to 65° C., and the aging time is 12 to 24 hours.
8. A microspherical TiO as claimed in any one of claims 1 to 7 2-x / C / FeMn-LDH S A composite photo-Fenton catalyst prepared by the preparation method of / g-C3N4 composite photo-Fenton catalyst.
9. Use of the composite photo-Fenton catalyst as claimed in claim 8 in catalytic degradation of ammonia nitrogen and lipophilic antibiotics in sewage or sludge tail water.
10. The use according to claim 9, characterized in that The antibiotics include quinolone antibiotics, macrolide antibiotics, tetracycline antibiotics or sulfonamide antibiotics.
Citation Information
Patent Citations
Preparation method of nano TiO2 / g-C3N4 photocatalytic material
CN113828294A
PREPARATION METHOD AND APPLICATION OF g-C3N4 / (101)-(001)-TiO2 COMPOSITE MATERIAL
AU2020102640A4
Composite optical anode of dye -sensitized solar cell
CN102157273A